Implementasi Pendekatan Rational Emotive Behavior Therapy (REBT) dalam Membantu Mengatasi Kebiasaan Terlambat Siswa SMA Negeri 6 Model Lubuklinggau - Desy Seplyana (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2019)
The purpose of this study are: 1. Describe the application of Rational-Emotive Behavior Therapy (REBT) in helping to overcome late student habits, 2. Help overcome late habits models of SMA 6 Lubuklinggau through Rational-Emotive Behavior Therapy (REBT). This type of research is Counseling Guidance Action Research. The research subjects were Grade X and XI students of SMA Negeri 6 Model Lubuklinggau with 10 students. Data analysis uses qualitative techniques. research result; 1. The principal is expected to make policies to support the process of implementing an appropriate guidance and counseling program; 2. Counseling teachers carry out the task of solving the problem of late school habits through the process of Rational-Emotive Behavior Therapy (REBT) counseling.